2013
DOI: 10.1016/j.astropartphys.2013.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Searches for large-scale anisotropies of cosmic rays: Harmonic analysis and shuffling technique

Abstract: The measurement of large scale anisotropies in cosmic ray arrival directions is generally performed through harmonic analyses of the right ascension distribution as a function of energy. These measurements are challenging due to the small expected anisotropies and meanwhile the relatively large modulations of observed counting rates due to experimental effects. In this paper, we present a procedure based on the shuffling technique to carry out these measurements, applicable to any cosmic ray detector without a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In addition to the CMB, probes that show anisotropy include radio sources [144][145][146][147][148], LX-T scaling [149], short gamma ray bursts [150], acceleration rates [151][152][153], Ia supernova [118,154], distribution of galaxy morphology types [155], dark energy [151,[156][157][158], fine structure constant [159], galaxy motion [160], H o [161], polarization of quasars [162][163][164][165][166], and cosmic rays [167][168][169][170]. It has also been shown that the large-scale distribution of galaxies in the Universe is not random [171], and it could have a preferred direction [66,71,73,77,[172][173][174][175][176][177].…”
Section: Large-scale Structure Explanationmentioning
confidence: 99%
“…In addition to the CMB, probes that show anisotropy include radio sources [144][145][146][147][148], LX-T scaling [149], short gamma ray bursts [150], acceleration rates [151][152][153], Ia supernova [118,154], distribution of galaxy morphology types [155], dark energy [151,[156][157][158], fine structure constant [159], galaxy motion [160], H o [161], polarization of quasars [162][163][164][165][166], and cosmic rays [167][168][169][170]. It has also been shown that the large-scale distribution of galaxies in the Universe is not random [171], and it could have a preferred direction [66,71,73,77,[172][173][174][175][176][177].…”
Section: Large-scale Structure Explanationmentioning
confidence: 99%
“…dx , d y , and d z considering the effect of the limited exposure(Deligny & Salamida 2013; see also K-inverse method explained inDing et al 2019). The dipole components d e,iä(x,y,z) for each of the three energy bins are then compared to the measured…”
mentioning
confidence: 99%
“…with Ñ = i 1/ω r (α i ). The uncertainty on the recovered coefficients then reads, still in the case of small anisotropies [40], as…”
Section: Harmonic Analysis In Right Ascensionmentioning
confidence: 99%